Misconception about ultrasound among Nigeiran women attending specialist and tertiary health institutions in Ibadan (2012)
Background: In women health, ultasound is well established as a safe tool, and it is often the first imaging modality employed in the, screening, investigation and treatment of conditions in obstetrics and gynaecology. However, women's misconceptions about health issues, aetiology and treatment of diseases conditions may have negetive impact on thier health care seeking behaviour. Client's perspective of diagnosis including investigation process is therefore crucial in health care. This study aimed at finding out the misconceptions expressed by clients about ultrasound, and the potential predictors associated with this attitude among women in Nigeria. Method: A descriptive cross-sectional survey was conducted among 3137 women who presented for transabdominal ultrasound scan between August and November 2010 in two referral hospitals in Nigeria. Data were obtained using a questionnaire. Descriptive and multivariate analysis was performed applying logistic regression analysis; predictors of misconceptions expressed by clients about ultrasoung, and misconception among women in Nigeria were identified using SPSS statistics (SPSS Inc, Chicago, IL) version 17 software. Results: The mean age of the women was 33.8 years (standard deviation=7.0), with 88.8% currently married. More than half of the respondents had tertiary education (56.6%), followed by secondary school education (34.5%), primary education(7.8%) and no formal education (1.1%). There were 59 women who held the misconception that ultrasound was dangerous to health accounting for 1.9% of the study population. The reasons given by this group of women included; 'ultrasound can kill or destroys the body cells'(35.6%); 'it can cause cancer' (15.3%); 'the radiation is only dangerous to some organs of the body' (6.8%); 'it can harm or deform the fetus'(6.7%); 'it is only dangerous when exposure is frequent'(5.1%) and 'only dangerous when handled by unskilled medical personnel' (1.7%). Conclusion: This study provides insight to the wide range of issues about clients' perception and misconception regarding ultrasound safety. These issues have to be addressed to improve better compliance and patronage about ultrasound scans in Nigeria. We suggest that robust conseling sessions is imperative to address all the views and possible concerns of clients to improve better service delivery.